The attitudes of medical and nursing school students towards alcohol and drug consumption - Ersoy, M. A.; Özdemir, N.; Savaş, H. A. (Journal of Dependence, 2008)
Objective: Negative attitudes toward alcohol and substance use are common and have negative effects on the treatment process. This study aimed to investigate the attitudes of nursing students at medical schools and health colleges toward alcohol and substance use. Method: A total of 425 subjects, consisting of nursing students at medical schools and health colleges, were included in the study. The relationship between attitudes toward alcohol and substance use, sociodemographic variables, and individual and family history of alcohol and substance use was examined. Findings: The scale items used in the study were subjected to psychometric evaluation, and the resulting 21-item scale had a Cronbach's alpha of 0.871 and a Guttman split-half consistency coefficient of 0.775, indicating acceptable levels. Nursing and medical students did not differ in terms of attitudes. It can be said that stigmatizing attitudes among students receiving health education are at a significant level. Those with higher incomes and higher-class degrees have less negative attitudes. Those with a personal or family history of alcohol and substance use were found to have lower levels of stigmatizing attitudes. Conclusion: Although these results indicate that education is somewhat effective in reducing negative attitudes, it would be appropriate to develop educational programs aimed at reducing negative attitudes.
Keywords: alcohol; substance use; student